Assessment and examinations in religious education: sixty years of research and analysis - Fancourt, N (Routledge, 2016)
In the broad field of educational research, there is a common view that education consists of three domains: curriculum, i.e. the content of what is taught, such as the disciplines of knowledge and intellectual skills; pedagogy, i.e. the processes of teaching and learning, such as the role and nature of classroom interaction; assessment, i.e. the methods of evidencing that the learning has occurred, including public examinations. In research about religious education, there has been considerable attention to curriculum, notably in defining the religion(s) and skills to be learnt, and some attention to pedagogy, for example in terms of classroom talk and dialogue; over the years assessment has received somewhat less attention, but is increasingly in the spotlight. This virtual special edition – the first ever in British Journal of Religious Education - takes stock of the past by presenting some of the research and scholarship on assessment, notably including examinations, which has previously been published in this journal (or its antecedent publications) from the 1950s onwards.